Never touch a grumpy bat! - Rosie Greening (Tennessee; Make Believe Ideas Ltd., 2020)
"You must never touch a grumpy bat ... except in this book! The Halloween friends are feeling grumpy! See if you can cheer them up in this rhyming book, and have fun touching the bumpy characters ... if you dare!"
Keywords: Board books